Principal Leadership Management in Improving Teacher’s Performance - Tini Yaparaduna; Bukman Lian; Pahlawan Pahlawan (Yayasan Sembilan Pemuda Indonesia, 2027)
This study aims to describe and analyze the leadership management of school principals in improving teacher performance at SD Negeri 01 Tanjung Kukuh through four management stages: planning, implementation, evaluation, and follow-up. A descriptive qualitative approach was employed. Data were collected through in-depth interviews with principals and teachers, participatory observation of leadership behavior and teaching performance, and documentation studies of learning tools and supervision reports. Analysis followed Miles and Huberman's interactive model, encompassing data reduction, data display, and conclusion drawing. Findings reveal that: (1) planning is conducted collaboratively, involving teachers in vision formulation and supervision scheduling; (2) implementation occurs through technical guidance, motivational awards, and exemplary principal discipline; (3) evaluation is carried out via periodic clinical supervision to monitor alignment between lesson plans and classroom practice; and (4) follow-up is realized by facilitating teachers' sustainable professional development through workshops and teacher working groups (KKG) to address identified obstacles. This study provides a holistic, stage-by-stage model of integrated leadership management in a rural elementary context, an approach rarely documented in Indonesian school leadership literature. Findings offer a replicable framework for principals seeking to systematically enhance teacher professionalism through structured, participatory, and reflective management practices. This research contributes empirical evidence that integrated leadership management across all four stages effectively improves teacher performance, demonstrating that collaborative planning, supportive implementation, clinical evaluation, and targeted follow-up are mutually reinforcing strategies for sustainable educational quality improvement.